KEMAMPUAN MATEMATIKA LAKI-LAKI DAN PEREMPUAN - Asmaningtias, Yeni Tri (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
Student’s mathematic capability is divide into two is that verbally mathematic capability and mathematic capability spatially. Spatial understanding includes capability to think through mental figure transformation. Spatial mindset is different from type of alternative information process suggesting that activity of thinking deductively, logically, and linearly, accessed through verbal system. Many mathematic problems can be solved by picturing solution diagram (spatial solution) or by making algorithm solution step by step (logic-deductive and verbal solution). Arithmetic on adult is located on field of language process in the brain, whereas calculation is controlled by visual spatial system. Solution of spatial mechanic mathematic problem is loved by male child more than strategy loved highly by female child, so that the research conducted by TIMSS suggests that male student has spatial mathematic capability whereas female student has verbal mathematic capability. Keyword: mathematic ability, male, female.